Transformation of Human Resource Capacity in MSMEs through Innovation, Digitalization, and Strategic Partnerships as Drivers of Community Economic Welfare in Tourism Villages - Susantinah Wisnujati, Nugrahini; Rijal, Syamsu (PT. LITERASI SAINS NUSANTARA, 2025)
This study aims to analyze the transformation of human resource (HR) capacity in Micro, Small, and Medium Enterprises (MSMEs) through innovation, digitalization, and strategic partnerships as drivers of community economic welfare in tourism villages. The research method employed is a literature review with a qualitative approach, focusing primarily on providing additional references related to community service. Data were collected from scholarly articles published on Google Scholar and credible websites within the timeframe of 1964–2025. Out of 50 articles gathered, a strict selection based on relevance and quality yielded 23 articles that were further analyzed using qualitative descriptive analysis. The findings reveal that innovation drives creativity and product differentiation in tourism village-based MSMEs, digitalization expands market access and improves operational efficiency, while strategic partnerships strengthen networking, knowledge transfer, and access to broader resources. These three factors collectively support the enhancement of MSME HR capacity, directly contributing to income growth, job creation, and collective community welfare in tourism villages. The study contributes theoretically by reinforcing the integration of Human Capital Theory, Diffusion of Innovation Theory, Technology Acceptance Model, Resource-Based View, and Community Development Theory, while also providing practical contributions as additional references for developing community service programs focused on empowering tourism village MSMEs.